Generation of Rag1‐knockout immunodeficient rats and mice using engineered meganucleases. Issue 2 (12th November 2012) - Ménoret, Séverine; Fontanière, Sandra; Jantz, Derek; Tesson, Laurent; Thinard, Reynald; Rémy, Séverine; Usal, Claire; Ouisse, Laure‐Hélène; Fraichard, Alexandre; Anegon, Ignacio
Abstract : Despite the recent availability of gene‐specific nucleases, such as zinc‐finger nucleases (ZFNs) and transcription activator‐like nucleases (TALENs), there is still a need for new tools to modify the genome of different species in an efficient, rapid, and less costly manner. One aim of this study was to apply, for the first time, engineered meganucleases to mutate an endogenous gene in animal zygotes. The second aim was to target the mouse and rat recombination activating gene 1 ( Rag1 ) to describe, for the first time, Rag1 knockout immunodeficient rats. We microinjected a plasmid encoding a meganuclease for Rag1 into the pronucleus of mouse and rat zygotes. Mutant animals were detected by PCR sequencing of the targeted sequence. A homozygous RAG1‐deficient rat line was generated and immunophenotyped. Meganucleases were efficient, because 3.4 and 0.6% of mouse and rat microinjected zygotes, respectively, generated mutated animals. RAG1‐deficient rats showed significantly decreased proportions and numbers of immature and mature T and B lymphocytes and normal NK cells vs. littermate wild‐type controls. In summary, we describe the use of engineered meganucleases to inactivate an endogenous gene with efficiencies comparable to those of ZFNs and TALENs. Moreover, we generated an immunodeficient rat line useful for studies in which there is a need for biological parameters to be analyzed in the absence of immune responses.—Ménoret, S., Fontanière, S., Jantz, D., Tesson, L., Thinard, R., Rémy, S., Usal, C., Ouisse, L.‐H., Fraichard, A., Anegon, A. Generation of Rag1 ‐knockout immunodeficient rats and mice using engineered meganucleases. FASEB J. 27, 703–711 (2013). www.fasebj.org